Kinetic modeling of the aqueous copolymerization of acrylamide with N,N’-methylenebisacrylamide - Pinto, Virgínia (2011)
This research reports kinetic modeling studies concerning the synthesis of PAAm and acrylamide/N,N’-methylenebisacrylamide (AAm/BAAm) hydrogels, in a 2.5 L batch reactor, considering aqueous solution and water in oil inverse suspension polymerizations.